The impact of patient and doctor characteristics on the prescribing of low cost generic formulations in Brazil. (September 2014) - Stephens, Peter; Leufkens, Hubert
Objectives: To examine the impact of the characteristics of doctors and patients on the use of low cost generic formulations in Brazil in 2012. Setting: This study examined 17, 627 consultations in which a medicine known to have an unbranded generic formulation available was prescribed. These consultations were generated by a sample of 723 doctors working in both public and private sectors in 2012. Results: 74% of doctors prescribed both branded and unbranded formulations. Only 8/723 doctors never prescribed a generic of any sort. Doctors were found to prescribe less expensive formulations of medicines to those patients with co-morbid conditions and those needing treatment with higher priced medicines. Increasing patient age was significantly associated with less expensive formulations. Conclusion: This study indicates that Brazil is a relatively mature generic market with most doctors prescribing a generic formulation. Doctors prescribe formulations that are relatively less expensive where the absolute price of the medicine is higher and where the patient is older or being treated for more than one diagnosis. This suggests that the economic burden of treatment may be being taken into account.